Cooccurrence of Metastatic Papillary Thyroid Carcinoma and Salmonella Induced Neck Abscess in a Cervical Lymph Node - Jae-Myung Kim; Ju-Yeon Kim; Eun Jung Jung; Eun Jin Song; Dong Chul Kim; Chi-Young Jeong; Young-Tae Ju; Young-Joon Lee; Soon-Chan Hong; Sang-Kyung Choi; Woo-Song Ha (Case Reports in Medicine)
Cervical lymph node metastasis is common in patients with papillary thyroid carcinoma (PTC). Salmonella species are rarely reported as causative agents in focal infections of the head and neck. The cooccurrence of lymph node metastasis from PTC and a bacterial infection is rare. This report describes a 76-year-old woman with a cervical lymph node metastasis from PTC and Salmonella infection of the same lymph node. The patient presented with painful swelling in her left lateral neck region for 15 days, and neck ultrasonography and computed tomography showed a cystic mass along left levels II–IV. The cystic mass was suspected of being a metastatic lymph node; modified radical neck dissection was performed. Histopathological examination confirmed the presence of PTC in the resected node and laboratory examination of the combined abscess cavity confirmed the presence of Salmonella Typhi. Following antibiotic sensitivity testing of the cultured Salmonella Typhi, she was treated with proper antibiotics. Cystic lesions in lymph nodes with metastatic cancer may indicate the presence of cooccurring bacterial infection. Thus, culturing of specimen can be option to make accurate diagnosis and to provide proper postoperative management.